Continuous flow aqueous tandem conversion of trans-ferulic acid into high added value chemicals - Kelvin Adrian Sanoja-López; Rafael Luque (Results in Engineering)
This study focuses on the multi-stage tandem valorization of trans-ferulic acid (t-FA) into high value-added products using a 10 % Pd/C catalytic process in continuous flow under mild operating conditions. The results demonstrate the selective conversion of t-FA to 4-ethylguaiacol and 4-vinylguaiacol with good yields under mild conditions and short reaction times. Additionally, acetovanillone was obtained through the addition of hydrogen peroxide to the studied conditions. This continuous flow approach offers several advantages over batch methods, including the ability to achieve high yields with precise control of parameters such as temperature, pressure, and flow rate, thereby facilitating process optimization and scalability.